Giant excitonic upconverted emission from two-dimensional semiconductor in doubly resonant plasmonic nanocavity - Qi, Pengfei (2023)
Phonon-assisted upconverted emission is the heart of energy harvesting, bioimaging, optical cryptography, and optical refrigeration. It has been demonstrated that emerging two-dimensional (2D) semiconductors can provide an excellent platform for efficient phonon-assisted upconversion due to the enhanced optical transition strength and phonon-exciton interaction of 2D excitons. However, there is little research on the further enhancement of excitonic upconverted emission in 2D semiconductors. Here, we report the enhanced multiphoton upconverted emission of 2D excitons in doubly resonant plasmonic nanocavities. Owing to the enhanced light collection, enhanced excitation rate, and quantum efficiency enhancement arising from the Purcell effect, an upconverted emission amplification of >1000-fold and a decrease of 2~3 orders of magnitude in the saturated excitation power are achieved. These findings pave the way for the development of excitonic upconversion lasing, nanoscopic thermometry, and sensing, revealing the possibility of optical refrigeration in future 2D electronic or excitonic devices.